Pneumothorax and pneumoperitoneum during the apnea test: how safe is this procedure? Pneumotorax y pneumoperitoneo durante el test de apnea: cuán seguro es este procedimiento? - GUSTAVO SAPOSNIK; GRACIELA RIZZO; JORGE L. DELUCA (Arquivos de Neuro-Psiquiatria)
Apnea test is a crucial requirement for determining the diagnosis of brain death (BD). There are few reports considering clinical complications during this procedure. We describe a major complication during performing the apnea test. We also analyse their practical and legal implications, and review the complications of this procedure in the literature. A 54 year-old man was admitted for impaired consciousness due to a massive intracerebral hemorrhage. Six hours later, he had no motor response, and all brainstem reflexes were negative. The patient fulfilled American Academy of Neurology (AAN) criteria for determining BD. During the apnea test, the patient developed pneumothorax, pneumoperitoneum, and finally cardiac arrest. Apnea test is a necessary requirement for the diagnosis of brain death. However, it is not innocuous and caution must be take in particular clinical situations. Complications during the apnea test could be more frequent than reported and may have practical and legal implications. Further prospective studies are necessary to evaluate the frequency and nature of complications during this practice. El test de apnea (AT) es un requerimiento esencial para el diagnóstico de muerte encefálica. Hay pocos estudios que consideren complicaciones clínicas relacionadas con este procedimiento. Describimos un paciente que desarrolló una complicación mayor mientras se efectuaba el test de apnea. Realizamos una revisión de las complicaciones relacionadas con este procedimiento en la literatura. CASO CLÍNICO: Un hombre de 54 años fue admitido por deterioro del sensorio debido a una hemorragia intracerebral. Seis horas posteriores, el paciente no tenía respuesta motora, y todos los reflejos del tronco cerebral estaban abolidos. El paciente cumplía con los criterios diagnósticos de Muerte Encefálica de acuerdo a lo establecido por la Academia Americana de Neurología. Durante el test de apnea, el paciente desarrolla súbitamente pneumotorax, pneumoperitoneo, y finalmente paro cardíaco. CONCLUSIÓN: El test de apnea es un requerimiento necesario para determinar el diagnóstico de muerte encefálica. No obstante, no es un procedimiento inocuo. Complicaciones durante este procedimiento pueden ser mas frecuentes que lo reportado en la literatura y tiene implicancias prácticas y legales.